Handbook of LC-MS Bioanalysis Best Practices, Experimental Protocols, and Regulations - Li, Wenkui;Ed. Zhang, Jie;Ed (John Wiley & Sons, 2013)
Consolidates the information LC-MS bioanalytical scientists need to analyze small molecules and macromolecules The field of bioanalysis has advanced rapidly, propelled by new approaches for developing bioanalytical methods, new liquid chromatographic (LC) techniques, and new mass spectrometric (MS) instruments. Moreover, there are a host of guidelines and regulations designed to ensure the quality of bioanalytical results. Presenting the best practices, experimental protocols, and the latest understanding of regulations, this book offers a comprehensive review of LC-MS bioanalysis of small m.